Studies On Exchange Equilibria And Its Prediction On Some Acid Soils Of Kerala - Swarnavi S (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1988)
More than 70 per cent of the upland soils of Kerala are acidic. The acidity of the soil is primarily associated with the presence of hydrogen and aluminium in exchangeable form. The soil solution aluminium in acid soil infertility clearly establishes the agronomic significance of aluminium ion equilibria in soils. The present study, entitled “Studies on exchange equilibria and its prediction on some acid soils of Kerala” was conducted to find out(1) the effect of different concentrations of aluminium in the electrolyte solution on exchange equilibria in soils (2) the influence of different cations on the free energy and various selectivity coefficients (3) the dependence of different selectivity coefficients on potassium, calcium and magnesium saturation of soils (4) the role of organic matter on cation exchange equilibria with special reference to potassium, calcium, magnesium and aluminium. Cation exchange equilibria involving aluminium- potassium, aluminium – calcium and aluminium- magnesium were studied in three soil types, viz., Kari, laterite and redloam soils, differencing in their texture and organic matter content. The normalized exchange isotherms for different soils and cationic systems were drawn and the results were interpreted in terms of different selectivity coefficients and approximate free energy change of the exchange reactions. From the study on the effect of different electrolyte concentration of aluminium on aluminium – potassium, aluminium- calcium and aluminium – magnesium exchange, an increasing aluminium adsorption was observed with an increase in electrolyte concentration of aluminium. The adsorption of aluminium was maximum in soils with high organic matter content. The normalized exchange isotherms of aluminium for different cationic systems and soils lay above the diagonal, suggested the preferential adsorption of aluminium over other cations. Except the Gapon selectivity coefficient, all the other coefficients (KKDO, KV and KN) increased upto a certain value of base saturation and then decreased. The value of KG increased with increase in base satuation. Among the various selectivity coefficients, KN was found to be the most dependent one and KG the least dependent. The dependence followed the order KN > KV > KKDO > KG. The negative values of free energy change for different cationic systems suggested the preferential adsorption of potassium, calcium and magnesium over aluminium. Among these cations potassium was found to be adsorbed with more energy, followed by calcium, magnesium, and then by aluminium. The values of free energy change showed the following order of preference for the competing cations: K > Ca > Mg > Al. From the study it can be concluded that potassic fertilizers can be effectively used in acid soils of Kerala, because of its high retention and minimum leaching loss. Compared to potassium, calcium and magnesium were adsorbed with less bond energy and hence to maintain a higher concentration of these cations in the soil exchanger, a considerable amount of calcium and magnesium should be supplied by frequent application of lime. To evaluate correctly the response of applied potassic fertilizers and liming material in different soils, efforts should be made to relate exchange behaviour of potassium, calcium and magnesium to the nature and relative proportion of different soil clay minerals. Similarly, the extension of the predictive approach essentially meant for binary system need special attention in order to make the studies on cation exchange equilibria more realistic and field oriented.